Efektifitas Penggunaan Video dalam Pembelajaran Istima' Bahasa Arab Model Penerapan Student Center Learning (SCL) dalam Pembelajaran Istima - Fina Aunul Kafi (STAIFAS-Press, 2018)
ABSTACT Listening is one of four competencies in language. Heading competence should be mastered by students in learning Arabic. The use of instructional media certainly provides convenience for teachers to hear Arabic. Use of media in the lesson istima' is very important because the oral should be played first from the original Arabic. Istima' learning requires the use of audiovisual as a medium of learning. The use of this video will be greeted enthusiastically by the students. With the use of this video the students listen carefully which is contained in the video in the form of Arabic conversations. After the spectacle was over, the class was divided into two groups or more for content questioning that was watched earlier. It is concequences for SCL type. From the process, there arise communicative interaction between students so they will continue try to listen more Arabic communication via video and understand it well. Keywords : istima’, competencies, video, learning SCL